Scent of stem cells: How can neurogenesis make us smell better? - Avaro, Vittoria; Hummel, Thomas; Calegari, Federico (Frontiers in Neuroscience, 2022)
Throughout the animal kingdom, olfaction underlies the ability to perceive chemicals in the environment as a fundamental adaptation with a plethora of functions. Unique among senses, olfaction is characterized by the integration of adult born neurons at the level of both the peripheral and central nervous system. In fact, over the course of life, Neural Stem Cells (NSC) reside within the peripheral olfactory epithelium and the brain’s subventricular zone that generate olfactory sensory neurons and interneurons of the olfactory bulb, respectively. Despite this unique hallmark, the role(s) of adult neurogenesis in olfactory function remains elusive. Notably, while the molecular signature and lineage of both peripheral and central NSC are being described with increasing detail and resolution, conflicting evidence about the role of adult born neurons in olfactory sensitivity, discrimination and memory remains. With a currently increasing prevalence in olfactory dysfunctions due to aging populations and infections such as COVID19, these limited and partly controversial reports highlight the need of a better understanding and more systematic study of this fascinating sensory system. Specifically, here we will address three fundamental questions: What is the role of peripheral adult neurogenesis in sustaining olfactory sensitivity? How can newborn neurons in the brain promote olfactory discrimination and/or memory? And what can we learn from fundamental studies on the biology of olfaction that can be used in the clinical treatment of olfactory dysfunctions?